2021
DOI: 10.1021/acs.langmuir.1c01282
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Bioinspired Scalephobic Surfaces with Specific Barrier Layers

Abstract: Bioinspired superwettable surfaces have been widely harnessed in diverse applications such as self-cleaning, oil/water separation, and liquid transport. So far, only a little work is focused on scalephobic capability of those superwettable surfaces. However, the troublesome scale deposition will inevitably be observed in our daily production and life, greatly reducing heat transfer efficiency and inhibiting the liquid transport. To address this annoying problem, as the emerging strategy, specific barrier layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…For the hydrophilic hydrogel, to be uniform and nonporous and to avoid delamination, the polymer content needs to be increased; however, a drawback of this approach is that the removal performance decreases, which can be mitigated by microtexturing the surface. We demonstrated coatings that had low adhesion to crystallization fouling deposits, one of the sought-after properties toward realizing intrinsically scalephobic surfaces ( 17 ). Specifically, we showed that by microtexturing soft hydrogel coatings, we can remove up to 98% of the crystallites, which is 66% better than rigid untreated substrate under the same shear flow conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the hydrophilic hydrogel, to be uniform and nonporous and to avoid delamination, the polymer content needs to be increased; however, a drawback of this approach is that the removal performance decreases, which can be mitigated by microtexturing the surface. We demonstrated coatings that had low adhesion to crystallization fouling deposits, one of the sought-after properties toward realizing intrinsically scalephobic surfaces ( 17 ). Specifically, we showed that by microtexturing soft hydrogel coatings, we can remove up to 98% of the crystallites, which is 66% better than rigid untreated substrate under the same shear flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness, applicability, and scalability of these techniques are limited ( 13 15 ). Researchers have investigated passive methods for repelling scale such as surface engineering, interfacial materials, and coatings, which can control the interaction between the scale and surface ( 16 , 17 ). These methods are considered attractive alternatives to achieve sustainability and cost-efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The nanostructure created an air layer inhibiting the deposition of calcium carbonate, while DTPMPA was continuously released to prevent the bonding of calcium ions with carbonates. This novel approach provides a promising avenue for developing antifouling coatings effective in both static and dynamic conditions [84][85][86].…”
Section: Biomimetic Microstructure Antifouling Coatingsmentioning
confidence: 99%
“…[ 7 ] On the other hand, surface engineering emerges as a supplementary and full‐passive approach capable of combating scaling problems at the source by orchestrating surface characteristics and crystallization mechanisms. [ 8 ] However, it is essential to note that the surface quality of the incompatible substrate will be compromised by external impacts or pressure. Thus, formation of stress concentration points can be a consequence of scratch and increased roughness and these issues can lead to premature failure.…”
Section: Introductionmentioning
confidence: 99%